The Utilization of Arbuscular Mycorrhizal Fungi for Planting Agarwood (Aquilaria spp) Seedling in Open Land - ABDURRANI MUIN (Microbiology Indonesia, 2019)
Agarwood is a type of semi-tolerant plant, so that for planting the seedlings should be grown under the shade. For planting in open land, it requires treatment in which one of them is using seedlings inoculated with arbuscular mycorrhizal fungi. The aim of the research is to obtain information on agarwood growth that has been inoculated with fungi mycorrhizal arbuscular when planted in the open land and ability to grow between agarwood seedlings inoculated mycorrhizal that was planted in the shade and in the open area. Split plot randomized block design was applied with treatments: the first plot consisting of plant had been inoculated with mycorrhizae and without mycorrhizal inoculation, and the sub plot was the types of shading that consists of open land, paranet 60 % intensity and natural vegetation. To reduce variabilty of site topographical differences were separated as bloks. Variables measured were: plant height (cm), stem diameter (mm), number of leaves, and survival percentage of plant. The results show that the height and diameter growth of seedlings innoculated with mycorrhizae were higher than non innoculated. The seedlings innoculated with mycorrhizal fungi were planted in the paranet shading grew better and significantly different compared to the vegetation shading. Seedlings innoculated mycorrhizal that were planted in open land grew better and significantly different compared to vegetation shading. This study results indicate that planting agarwood in the open land can be done using seedlings inoculated arbuscular mycorrhizal fungi. Key words: agarwood plant, arbuscular mycorrhizal fungi, shading and open land